Diagnosis and Management of Hypersensitivity to Antiplatelet Drugs: EAACI Position Paper - Cortellini, Gabriele; Nakonechna, Alla; Barbaud, Annick; Bavbek, Sevim; Calogiuri, Gianfranco; Doña, Inmaculada; Kvedariene, Violeta; Laguna Martinez, Jose Julio; Liberati, Serena; Pagani, Mauro; Romano, Antonino (Wiley, 2025)
Antiplatelet drug (APD) therapy is the cornerstone for the prevention of atherosclerotic cardiovascular disease. The main APDs are aspirin and thienopyridines, particularly clopidogrel. These drugs may induce hypersensitivity reactions (HSRs). The most common reported reactions to these drugs are cutaneous, such as exanthemas associated with thienopyridine and urticaria/angioedema by aspirin, which can also induce respiratory symptoms. APDs other than aspirin, particularly ticlopidine, can also cause hematologic reactions consisting mainly of isolated thrombocytopenia, agranulocytosis, and leukopenia. Immune-mediated reactions to aspirin are very rare. Few data suggest the usefulness of skin testing in patients with cutaneous reactions to APDs other than aspirin, particularly clopidogrel. Therefore, the drug provocation test is the gold standard for diagnosing hypersensitivity to APDs. Low-dose aspirin challenge (i.e., up to 150-180 mg) and aspirin desensitization have emerged as effective and safe approaches in patients with suspected or confirmed aspirin hypersensitivity who require aspirin therapy. Both, a short course of oral glucocorticoids without interruption of clopidogrel treatment and desensitization, appears to be effective and safe options in patients with cutaneous HSRs to clopidogrel. This position paper provides data and recommendations regarding the characteristics of HSRs to APDs and related diagnostic procedures in order to make them as safe and effective as possible. Management and treatment options, including desensitization protocols, are also provided.